(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was carried out in Valsad district of Gujarat to find the extent of adoption of improved dairy husbandry practices. A random sample of 240 dairy animal owners were selected and extent of adoption of improved dairy husbandry practices in six major aspects of housing, feeding, breeding, health care, milking and calf rearing management was studied. Proper orientation of animal shed (84.58%) and provision of proper floor space (85.63%) were more adopted in housing techniques. Provision of clean and fresh drinking water (87.08%), extra ration to advance pregnant animals (61.88%) and cultivation of green fodder (60.42%) were more adopted in feeding management. In breeding techniques, artificial insemination of animals (96.46%), keeping watch on oestrus cycle and heat symptoms of animals (84.58%) and breeding after 60-90 days of calving (79.38%) were more adopted by the dairy animal owners. Treatment of reproductive disorders (84.38%), proper cleaning and sanitation of shed (73.75%) and deworming of animals (57.92%) were more adopted by respondents in health care management techniques. In milking and calf rearing techniques, washing pails and hands before milking (98.96%), preparation of animals before milking (74.38%), attending newly born calf and proper cleaning of mucous from mouth and nostrils (98.75%), milk feeding to calf up to three months of age (96.88%) were more adopted by the dairy animal owners.